2018
DOI: 10.1002/14651858.cd009260.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Early intensive behavioral intervention (EIBI) for young children with autism spectrum disorders (ASD)

Abstract: Early intensive behavioral intervention (EIBI) for young children with autism spectrum disorders (ASD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
199
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(215 citation statements)
references
References 52 publications
6
199
0
10
Order By: Relevance
“…Therapists must use clinical decision making to choose which interventions to apply and to adapt treatment protocols for children who do not respond (Sherer & Schreibman, 2005;Stahmer, Schreibman, & Cunningham, 2011). Although a few factors have been identified that tend to moderate treatment success, such as age, cognitive level, language ability, severity of autism symptoms, and presence of comorbidities (Reichow, Barton, Boyd, & Hume, 2012), very little information on adapting treatment approaches is available to assist clinicians in the choice or adoption of specific protocols for those who do not respond (Vivanti, Dissanayake, Zierhut, & Rogers, 2013) and who are most in need of treatment individualization (Schreibman, Dufek, & Cunningham, 2011). Essentially, nothing is known about how to individualize treatment protocols prospectively to maximize child responsiveness (Stahmer et al, 2011;Trembath & Vivanti, 2014).…”
Section: Strengths Preferences and Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapists must use clinical decision making to choose which interventions to apply and to adapt treatment protocols for children who do not respond (Sherer & Schreibman, 2005;Stahmer, Schreibman, & Cunningham, 2011). Although a few factors have been identified that tend to moderate treatment success, such as age, cognitive level, language ability, severity of autism symptoms, and presence of comorbidities (Reichow, Barton, Boyd, & Hume, 2012), very little information on adapting treatment approaches is available to assist clinicians in the choice or adoption of specific protocols for those who do not respond (Vivanti, Dissanayake, Zierhut, & Rogers, 2013) and who are most in need of treatment individualization (Schreibman, Dufek, & Cunningham, 2011). Essentially, nothing is known about how to individualize treatment protocols prospectively to maximize child responsiveness (Stahmer et al, 2011;Trembath & Vivanti, 2014).…”
Section: Strengths Preferences and Goalsmentioning
confidence: 99%
“…Even within the constrained paradigm of the early intensive behavioral intervention (EIBI) model for ASD (Lovaas, 1987), meta-analysis assigns a great deal of variability in outcome to the supervision provided to interventionists (Reichow & Wolery, 2009). Indeed, given the overall low quality of the empirical studies supporting EIBI, most reviewers emphasize the need for clinical decision making regarding its use (e.g., Reichow et al, 2012).…”
Section: Clinical Expertise Is Also a Critical Component In Provisionmentioning
confidence: 99%
“…Existing reviews of early treatment for ASD have focused exclusively on specific treatment models such as Applied Behavioural Analysis (Viru es-Ortega, 2010) or the Early Start Denver Model (Ryberg, 2015;Waddington, van der Meer, & Sigafoos, 2016), on treatment approaches more broadly, e.g. behavioural interventions (Reichow, Barton, Boyd, & Hume, 2012;Warren et al, 2011), or on a particular mode of delivery such as parent-mediated interventions (Nevill, Lecavalier, & Stratis, 2018;Oono, Honey, & McConachie, 2013). These reviews have varied in the age range included, from under 3 to 4 years to up to 12 years of age with most focusing on children younger than 6 years.…”
Section: Introductionmentioning
confidence: 99%
“…It is not possible at this time to reliably predict the clinical outcome of a heterozygous exonic NRXN1 deletion detected through prenatal testing. In these cases, it is advisable to set up a periodic neuro-behavioral follow-up program for the timely detection of warning signs and the prescription of early interventions possibly effective on neurodevelopmental deficits 89,90. It is also important to consider that NRXN1 deletion carriers reported in the Literature likely represent the severe end of a phenotypic spectrum and, as discussed above, NRXN1 deletions likely require "second-hit"genetic contributors, able to synergistically impair neurodevelopment and push phenotypic severity above clinical threshold.…”
mentioning
confidence: 99%